Resistance training to improve power and sports performance in adolescent athletes: A systematic review and meta-analysis - Harries, S. K.; Lubans, D. R.; Callister, R. (Journal of Science and Medicine in Sport, 2012)
Objectives: Resistance training in untrained adolescents can positively effect health-related fitness as well as improve muscular power and sports performance. The impact of resistance training on adolescent athletes is less clear. The purpose of this review is to determine the effectiveness of resistance training programs on muscular power and sports performance in adolescent athletes. Design: Systematic review and meta-analysis of previously published studies investigating resistance training in adolescent athlete populations. Methods: A systematic search of Medline, Embase, and SPORTDiscus databases was conducted on 21st March 2011 to identify studies evaluating resistance training programs on power and sports performance in adolescent athletes. Results: Thirty-four studies were identified. All but two of the studies reported at least one statistically significant improvement in an alactic muscular power outcome. The most common indicators of alactic power were vertical jump (25 studies) and sprint running (13 studies) performance. Fourteen studies provided data to allow for pooling of results in a meta-analysis. A positive effect was detected for resistance training programs on vertical jump performance (mean difference 3.08 [95% CI 1.65, 4.51], Z = 4.23 [P < 0.0001]). Conclusions: There is sufficient evidence to conclude that resistance-training interventions can improve muscular power in adolescent athletes. A positive effect on sports performance attributable to participation in resistance training was reported by almost half the included studies, however limited objective evidence to support these claims was found. Improvements in motor performance skills, such as jumping, are widely stated as indicators of improvements in sporting performance.